2018
DOI: 10.3390/jcm7110425
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on the Impact of Thrombolytic Therapy in Liver Transplantation Following Donation after Circulatory Death

Abstract: Aim: The livers from DCD (donation after cardiac death) donations are often envisaged as a possible option to bridge the gap between the availability and increasing demand of organs for liver transplantation. However, DCD livers possess a heightened risk for complications and represent a formidable management challenge. The aim of this study was to evaluate the effects of thrombolytic flush in DCD liver transplantation. Methods: An extensive search of the literature database was made on MEDLINE, EMBASE, Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…This treatment concept has shown promise in DCD liver transplantation as patients whose grafts were flushed with t-PA had significantly decreased ischemic biliary injuries and re-transplantation rate, as well as, better one-year graft survival. 35 The COVID-19 pandemic has demonstrated that patients with a low fibrinolytic activity on TEG can harbor an extremely high rate of renal failure requiring dialysis. 36 Autopsy series have demonstrated microvascular clots in organs of patients that have died from COVID-19 from multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment concept has shown promise in DCD liver transplantation as patients whose grafts were flushed with t-PA had significantly decreased ischemic biliary injuries and re-transplantation rate, as well as, better one-year graft survival. 35 The COVID-19 pandemic has demonstrated that patients with a low fibrinolytic activity on TEG can harbor an extremely high rate of renal failure requiring dialysis. 36 Autopsy series have demonstrated microvascular clots in organs of patients that have died from COVID-19 from multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…21,24 A description of the approaches for tPA administration in DCD liver transplant has been described in detail elsewhere. 25 The more recent studies using tPA showed improved 1-and 3-year patient and graft survival and a significant reduction in IC relative to controls. 21,24 These studies did not show the same increased transfusion requirement previously described by Hashimoto and colleagues.…”
Section: Thrombolytic Medications During Dcd Transplantationmentioning
confidence: 97%
“…Seminars in Liver Disease studies (two from the same institution) and one conference abstract with a prospective randomized/nonrandomized study, all of which described tPA protocols. 54 Two of these retrospective studies demonstrated a reduction in the incidence of IC/ischemic-type biliary lesions following adoption of a tPA protocol, while the third retrospective study and the randomized study demonstrated no difference. 9, [55][56][57] Although the authors of the two positive studies showed a significant reduction in the incidence of IC, they acknowledged that other changes in both procurement technique and patient selection occurred between the two compared era cohorts.…”
Section: Tissue Plasminogen Activatormentioning
confidence: 99%